Evolutionary Signature of Ancient Parasite Pressures, or the Ghost of Parasitism Past - Poulin, Robert; Bennett, Jerusha; de Angeli Dutra, Daniela; Doherty, Jean-François; Filion, Antoine; Park, Eunji; Ruehle, Brandon (Frontiers in Ecology and Evolution, 2020)
Animals adopt a range of avoidance strategies to reduce their exposure to parasites and the associated cost of infection. If strong selective pressures from parasites are sustained over many generations, avoidance strategies may gradually evolve from phenotypically plastic, or individually variable, to fixed, species-wide traits. Over time, host species possessing effective infection avoidance traits may lose parasite species. Indeed, if overcoming the avoidance strategies of a host species is too costly, i.e. if individuals of that species become too rarely encountered or difficult to infect, a generalist parasite may opt out of this particular arms race. From the host’s perspective, if avoidance traits are not costly or have been co-opted for other functions, they may persist in extant species even if ancestral parasites are lost, as signatures of past selection by parasites. Here, we develop the ‘ghost of parasitism past’ hypothesis. We discuss how animal species with a lower number of parasite species than expected based on their ecological properties or phylogenetic affinities are a good starting point in the search for traces of past parasite-mediated selection. We then argue that the hypothesis explains the dynamic and inconsistent nature of the relationship between the expression of avoidance traits and relative infection risk in comparative analyses across host species. Finally, we propose some approaches to test the predictions of the hypothesis. Animal morphology and behavior show clear evidence of past selective pressures from predators; we argue that past selection from parasites has also left its imprint, though in more subtle ways.